2023
DOI: 10.1136/gpsych-2023-101063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender on the association between cumulative cardiovascular risk factors and depression: results from the US National Health and Nutrition Examination Survey

Abstract: BackgroundThe comorbidity of cardiovascular disease (CVD) and depression has been well established, as depression usually presents simultaneously with CVD risk factors. However, the potential association between cumulative exposure to CVD risk and depression remains unclear, so we conducted the current investigation. To our knowledge, this is the first study that employs the cumulative risk model to examine the effect of CVD risk factors on depression using nationally representative population and gender, age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In addition, some studies have used cumulative risk models to clarify that many CVD risk factors have certain effects on depression. 37 However, each CVD was robustly associated with antidepressant use, including a 74% increased likelihood of antidepressant use associated with overall CVD. The reason behind the increased probability of using antidepressants due to CVD, without a corresponding increase in MDD, can be attributed to two factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have used cumulative risk models to clarify that many CVD risk factors have certain effects on depression. 37 However, each CVD was robustly associated with antidepressant use, including a 74% increased likelihood of antidepressant use associated with overall CVD. The reason behind the increased probability of using antidepressants due to CVD, without a corresponding increase in MDD, can be attributed to two factors.…”
Section: Discussionmentioning
confidence: 99%
“…(2) We further investigated the stability of the mediating effect of sleep disturbance by including medications used for treating sleep disturbance as covariates. (3) Given that the risk of depression in women is approximately twice that in men ( 29 ) and that research has indicated that there are sex differences in the association between depressive symptoms and CVD ( 30 ), we further explored the mediating role of sleep disturbance across both sexes. (4) Finally, considering that late-life depression is a complex, heterogeneous syndrome closely associated with numerous severe health consequences ( 31 ), we validated the mediating effects of sleep disturbance after stratification by age (younger than 60 years of age and 60 years and older).…”
Section: Methodsmentioning
confidence: 99%
“…[17] MR is becoming an increasingly powerful tool in epidemiology and human biology. Genomic wide association studies (GWAS) are often used to determine genetic variants to be investigated in MR. Depression is reported to be associated with several traditional cardiovascular risk factors, [18,19] such as smoking behavior, [20] physical activity, [21] and obesity. [22] Also, these factors are thought to be associated with hypercholesterolemia risk in various studies.…”
Section: Introductionmentioning
confidence: 99%